The Trade Between the European Union and the United Kingdom After Brexit and Its Impact on the Labour Market - Jankóová, Simona; Bolotov, Ilya; Hrubý, Michal; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis examines the trade relations between the European Union and the United Kingdom after Brexit, with a focus on its impact on the labour market. It explores how the United Kingdom's withdrawal from the European Union has influenced trade volumes and employment, taking into account key macroeconomic indicators such as GDP, unemployment, the state budget, inflation, and the exchange rate, as well as changes in trade policies and the introduction of new barriers. The thesis also addresses how these changes have affected labour mobility, skills shortages, and employment in selected sectors and regions. The research is based on secondary data from official and academic sources and covers the period from 2010 to 2024 to allow for a comparison of the pre- and post-Brexit situation. The aim is to provide a comprehensive overview of the trade and labour market developments brought about by Brexit for both the European Union and the United Kingdom.
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses